Mycelial Growth of Ganoderma curtissii in Locally Indigenous Media - Bellere, A D (KnE Social Sciences, 2018)
Fungal study requires culture medium for evaluation of its mycelial form and storing viable cell lines. In this study innovative media such as coconut water from matured nuts (CW), corn grit (CG) and rice bran (RB) decoction was evaluated. The ideal media for luxuriant growth of Ganoderma curtissii was coconut water media at physical condition of 26.40